Smoking and Teeth Loss - D. Hrubá; V. Vondráček; N. Salah; F. L. Alradhi (Czech Dental Chamber, 2014)
Background: Smoking is the most important single preventable risk factor for many diseases, including impaired oral health. Many studies have repeatedly documented the higher prevalence of caries, periodontitis, tooth loss and head-neck cancer among smokers.Smoking can contribute to the initiation and progression of diseases in oral cavity both indirectly (by smokers' bad nutrition and oral hygiene) and directly. The deleterious effect of smoking in the oral cavity is due to plaque accumulation and increased alveolar bone resorption. Main causal pathways are hypoxemia, inflammation, impaired immunity, mineral and bacterial imbalance. Cytotoxic effect of tobacco smoke on human gingival fibroblasts decreases their capacity for adhesion and proliferation. Compared to no-smokers, the outcome of implant treatment is among smokers usually less successful, as it is associated with many complications and poor healing. Conclusion: In many developed countries, dentists are active in the support of no-smoking behaviour and in motivation their smoking patients to smoking cessation. Such approach may be the challenge also for dentists in the Czech Republic.